EMS communication routings' optimisation to enhance power system security considering cyber‐physical interdependence. Issue 1 (4th January 2018) - Guo, Qinglai; Xin, Shujun; Xu, Luo; Sun, Hongbin
Abstract : Energy management system (EMS) is one of the most essential categories of the advanced applications in current cyber‐physical power systems. However, because of the tight coupling relationship between a power network and EMS's communication network, a physical break‐line fault may be accompanied by a communication line outage, which may result in regional unobservability and uncontrollability. To maximally avoid and eliminate such operation risks, referring to current EMS's 'active + standby' communication configuration scheme in China, the authors propose a dynamic routing optimisation mechanism for its standby communication routings, assigning the most reliable communication lines to the most important information. Such optimisation considers two factors: information's significance and the reliability of communication lines. By introducing cyber‐physical sensitivity index and path‐branch incidence matrix, both factors can be expressed numerically. In the case study, the authors optimise the standby communication routings for a power flow corrective control application under different scenarios. The results verify the effectiveness and superiority of their approach.